2012
DOI: 10.1016/j.mam.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding age-related macular degeneration (AMD): Relationships between the photoreceptor/retinal pigment epithelium/Bruch’s membrane/choriocapillaris complex

Abstract: There is a mutualistic symbiotic relationship between the components of the photoreceptor/retinal pigment epithelium (RPE)/Bruch’s membrane (BrMb)/choriocapillaris (CC) complex that is lost in AMD. Which component in the photoreceptor/RPE/BrMb/CC complex is affected first appears to depend on the type of AMD. In atrophic AMD (~85–90% of cases), it appears that large confluent drusen formation and hyperpigmentation (presumably dysfunction in RPE) are the initial insult and the resorption of these drusen and los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
674
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 825 publications
(747 citation statements)
references
References 181 publications
(228 reference statements)
14
674
0
17
Order By: Relevance
“…This is consistent with the finding that photoreceptor and RPE degenerate in a horse-shoe-shaped pattern surrounding the fovea as mentioned above, 15 regardless of the timing of events (does RPE atrophy occur first or does CC degeneration precede RPE atrophy?) and of the form of AMD (dry AMD or combined CNV and GA).…”
Section: Before the Anti-vegf Erasupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the finding that photoreceptor and RPE degenerate in a horse-shoe-shaped pattern surrounding the fovea as mentioned above, 15 regardless of the timing of events (does RPE atrophy occur first or does CC degeneration precede RPE atrophy?) and of the form of AMD (dry AMD or combined CNV and GA).…”
Section: Before the Anti-vegf Erasupporting
confidence: 91%
“…'RPE atrophy vs choroidal atrophy' in AMD According to Bhutto and Lutty 15 there is a 'mutualistic symbiotic relationship' between the components of the photoreceptor/RPE/Bruch's membrane/CC complex and subsequently between degenerating RPE and CC. Lutty's lab team had previously shown that at least in advanced dry AMD (GA), RPE atrophy occurs first, followed by CC degeneration, whereas CC degeneration precedes RPE atrophy in wet AMD.…”
Section: Before the Anti-vegf Eramentioning
confidence: 99%
“…In advanced nonneovascular AMD, geographic atrophy (GA) is associated with loss of photoreceptors, RPE, and the choriocapillaris. Whether the RPE or choriocapillaris alterations are the primary event in pathogenesis has been a matter of debate (26). Histologic studies have described choriocapillaris dysfunction in the intermediate stage of AMD, before development of GA or choroidal neovascularization (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…91,92 The pathogenesis of AMD is strongly associated with oxidative stress. 10,18,20,93,94 Currently, there is no established prevention or therapy for early AMD. The Age-Related Eye Disease Study (AREDS) is among the largest and most robust randomized clinical trials designed to investigate the role of daily oral supplementation of antioxidant vitamins and minerals.…”
Section: Discussionmentioning
confidence: 99%